3-Nitrooxypropanol substantially decreased enteric methane emissions of dairy cows fed true protein- or urea-containing diets - García, Florencia; Muñoz, Camila; Martínez Ferrer, Jorge; Urrutia, Natalie L.; Martínez, Emilio D.; Saldivia, Marcelo; Immig, Irmgard; Kindermann, Maik; Walker, Nicola; Ungerfeld, Emilio M. (Elsevier, 2022)
Methane is a potent but short-lived greenhouse gas targeted for short-term amelioration of climate change, with enteric methane emitted by ruminants being the most important anthropogenic source of methane. Ruminant production also releases nitrogen to the environment, resulting in groundwater pollution and emissions of greenhouse gas nitrous oxide. We hypothesized that inhibiting rumen methanogenesis in dairy cows with chemical inhibitor 3-nitrooxypropanol (3-NOP) would redirect metabolic hydrogen towards synthesis of microbial amino acids. Our objective was to investigate the effects of 3-NOP on methane emissions, rumen fermentation and nitrogen metabolism of dairy cows fed true protein or urea as nitrogen sources. Eight ruminally-cannulated cows were fed a plant protein or a urea-containing diet during a Control experimental period followed by a methanogenesis inhibition period with 3-NOP supplementation. All diets were unintentionally deficient in nitrogen, and diets supplemented with 3-NOP had higher fiber than diets fed in the Control period. Higher dietary fiber content in the 3-NOP period would be expected to cause higher methane emissions; however, methane emissions adjusted by dry matter and digested organic matter intake were 54% lower with 3-NOP supplementation. Also, despite of the more fibrous diet, 3-NOP shifted rumen fermentation from acetate to propionate. The post-feeding rumen ammonium peak was substantially lower in the 3-NOP period, although that did not translate into greater rumen microbial protein production nor lesser nitrogen excretion in urine. Presumably, because all diets resulted in low rumen ammonium, and intake of digestible organic matter was lower in the 3-NOP period compared to the Control period, the synthesis of microbial amino acids was limited by nitrogen and energy, precluding the evaluation of our hypothesis. Supplementation with 3-NOP was highly effective at decreasing methane emissions with a lower quality diet, both with true protein and urea as nitrogen sources.